2022
DOI: 10.3892/ol.2022.13580
|View full text |Cite
|
Sign up to set email alerts
|

Potential of blood exosomal ENAH, SEPT9, EGF, MMP‑9 and CXCL8 for the early screening of breast cancer

Abstract: Exosomal contents have been recognized as candidate biomarkers for cancer screening and prognosis. The current study aimed to evaluate the potential of the expression levels of exosomal enabled homolog (ENAH), septin 9 (SEPT9), epidermal growth factor (EGF), matrix metalloproteinase-9 (MMP-9) and C-X-C motif chemokine ligand 8 (CXCL8) in the blood for the early screening of breast cancer. Therefore, exosomes were extracted and purified from the peripheral blood of 47 patients with breast cancer, 63 disease con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In this study, the hybrid-based FS pipeline screened an optimal subset that includes three gene biomarkers, namely MAPK1, APOBEC3B, and ENAH, for earlier detection of primary breast tumors. In recent years, clinical studies have shown that these screened gene biomarkers, namely MAPK 1 [75][76][77][78][79][80], APOBEC3B [81][82][83][84], and ENAH [85][86][87][88], are known to be related to the pathophysiology of BC. Therefore, in addition to an unpaired t-test that characteristically focuses on each gene's differential expression between two classes of samples, we also focused on the differences in their ontology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the hybrid-based FS pipeline screened an optimal subset that includes three gene biomarkers, namely MAPK1, APOBEC3B, and ENAH, for earlier detection of primary breast tumors. In recent years, clinical studies have shown that these screened gene biomarkers, namely MAPK 1 [75][76][77][78][79][80], APOBEC3B [81][82][83][84], and ENAH [85][86][87][88], are known to be related to the pathophysiology of BC. Therefore, in addition to an unpaired t-test that characteristically focuses on each gene's differential expression between two classes of samples, we also focused on the differences in their ontology.…”
Section: Discussionmentioning
confidence: 99%
“…It assembles actin filaments for cell motility and adhesion [85]. Recent studies have shown the upregulated expression of ENAH in many human cancer types, namely breast cancer [86][87][88], melanoma [91], pancreatic cancer [92], and gastric cancer [93]. The overexpression of ENAH increases the chances of transformation and tumorigenesis in BC, consequently offering an innovative method of clinical evaluation of BC [94].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, MMP9 was found to be highly upregulated in tumour cell exosomes 48 . It has previously been shown that hepatocellular carcinoma-derived exosomes could increase MMP9 secretion in hepatocytes 5 49 Also, Zhang et al 50 have studied the potential of the expression levels of MMP-9 and CXCL8 in the blood for the early screening of breast cancer.…”
Section: Discussionmentioning
confidence: 99%